Prevalence and gender distribution of malocclusion among 13-15-year-old adolescents of Kerala, South India - Shobha Sundareswaran; Praveen Kizhakool (Wolters Kluwer Medknow Publications, 2019)
Objectives: To determine the prevalence and gender distribution of malocclusion in 13-15-year-old adolescents of Dravidian ethnicity, residing in urban and rural areas of Kerala, South India. Materials and Methods: A total of 1554 children (779 males, 775 females), from both urban and rural areas were examined in school settings. Survey proforma for personal details and occlusal registration according to Bjork et al. (1964) were used. Chi-square test was used for analysis. Results: Overall prevalence of malocclusion was 89.9% which included Angle's Class I, Class II (17.6%) and Class III (8%) malocclusions. Other anomalies detected were increased overjet (11.8%), anterior crossbite (27.5%), anterior open bite (1.6%), posterior crossbite (5.1%), scissor bite (4.4%), midline deviation (6.8%), bimaxillary protrusion (BMP-21.3%), crowding (66.6%), spacing (15.3%), rotations (45.4%), ectopic eruptions (11.1%), peg laterals (2.4%) and missing teeth (6.6%). Males showed a higher predilection for increased overjet, deep bite, spacing and missing teeth. Class III, BMP, midline deviations and rotations were found to be more prevalent among the rural group, whereas Class II, increased overjet, deep bite and ectopic eruptions were more prevalent among the urban. Conclusion: Information regarding the detailed pattern of malocclusion prevalence and the high prevalence of BMP among South Indian population of Kerala may provide a baseline data for planning orthodontic services.